Intelligent food packaging film containing lignin and cellulose nanocrystals for shelf life extension of food. (15th November 2022) - Halloub, Abdellah; Raji, Marya; Essabir, Hamid; Chakchak, Hind; boussen, Ratiba; Bensalah, Mohammed-ouadi; Bouhfid, Rachid; Qaiss, Abou el kacem
Abstract: The UV-protection films based on renewable materials extracted from natural sources are being one of the most interesting targets for the packaging industry. In this paper, the UV-protection films were produced based on modified lignin and cellulose nanocrystals, both were extracted from the Argania nutshell. The lignin was extracted via the alkylation process followed by chemical modification using epichlorohydrin. The chemical modification and the in-use temperature range of the films were investigated via FTIR and TGA, where the chemical modification of lignin improves the thermal property which is an essential parameter during the thermo-sealing of food packaging. On the other hand, the CNCs were extracted via acid hydrolysis treatment with the smallest size around 300 nm generating smooth texture of films. Finally, the produced films were shown a maximum absorption of the UV light in the range of 450–200 nm and great results in food packaging. Graphical abstract: Unlabelled Image